Early-onset intrahepatic cholestasis of pregnancy increased the incidence of gestational diabetes mellitus: a retrospective cohort study - Liu, Yaodan; Liu, Min; Liu, Jinghua; Sheng, Minmin; Hu, Zhenxia; Zhang, Xiaohong (Frontiers in Medicine, 2024)
Background Intrahepatic cholestasis of pregnancy (ICP) and gestational diabetes mellitus (GDM) are two common pregnancy complications that pose considerable health challenges. The interplay between these conditions is believed to significantly influence pregnancy outcomes, yet the nature of this relationship remains elusive. This study was designed to elucidate the connection between ICP and GDM. Methods This retrospective cohort study included 742 singleton pregnancies delivered at the Shanghai Public Health Clinical Center from January 2015 to December 2023. We compared the incidence of GDM and pregnancy outcomes between multiple ICP subgroups and a control group of healthy pregnancies. A multivariate regression model was used to measure the independent association between ICP and propensity for GDM development, as well as to assess the impact of potential bidirectional effects between ICP and GDM. Results The results indicate that the incidence of GDM is highest in the early-onset ICP (diagnosed before the 24th week of gestation) group compared to the control group and other ICP subgroups. Early-onset ICP is an independent risk factor for the development of GDM, with other risk factors including age, history of abortion, family history of diabetes, and elevated ALT levels. Subgroup interaction analysis did not reveal heterogeneity in the influence of early-onset ICP on the development of GDM across different subgroups. Further analysis showed that GDM itself does not increase the risk of late-onset ICP. Additionally, when comparing pregnancy outcomes between GDM patients with or without ICP, those with both GDM and ICP had significantly higher rates of preterm birth, cesarean section, and small for gestational age (SGA) compared to patients with GDM alone. Furthermore, elevated TBA levels (first diagnosed) of early-onset ICP patients were associated with an increased risk of GDM in a nonlinear fashion. Conclusion Our study indicated that early-onset ICP is significantly linked to an increased risk of GDM. Further research is warranted to explore the mechanisms behind this association and to develop strategies for early identification and intervention to mitigate GDM risk.